Numerical characterisation of one-step and three-step solar air heating collectors used for cocoa bean solar drying - Orbegoso E.M. (2017)
In the northern coastal and jungle areas of Peru, cocoa beans are dried using artisan methods, such as direct exposure to sunlight. This traditional process is time intensive, leading to a reduction in productivity and, therefore, delays in delivery times. The present study was intended to numerically characterise the thermal behaviour of three configurations of solar air heating collectors in order to determine which demonstrated the best thermal performance under several controlled operating conditions. For this purpose, a computational fluid dynamics model was developed to describe the simultaneous convective and radiative heat transfer phenomena under several operation conditions. The constructed computational fluid dynamics model was firstly validated through comparison with the data measurements of a one-step solar air heating collector. We then simulated two further three-step solar air heating collectors in order to identify which demonstrated the best thermal performance in terms of outlet air temperature and thermal efficiency. The numerical results show that under the same solar irradiation area of exposition and operating conditions, the three-step solar air heating collector with the collector plate mounted between the second and third channels was 67% more thermally efficient compared to the one-step solar air heating collector. This is because the air exposition with the surface of the collector plate for the three-step solar air heating collector former device was twice than the one-step solar air heating collector.